(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
Many Croatian scientists indicate that there are significant opportunities in tourism that can beneficially influence the overall socio-economic development of Croatia. It is recognised that Croatia has to follow more closely the contemporary tourism trends, in which much greater attention is given to ecology, the cultural identity of the destination, active vacations, service quality and selective forms of tourism development. There is also agreement that the clean sea, the coast, and the abundance of natural and cultural beauty are the advantages of Croatia’s tourism supply in the maritime part of the country. However, there are some discussions that the Continental part of Croatia is also abundant in natural beauty, cultural wealth, and gastronomy, and that it has many other underutilised tourism potentials. Different viewpoints on tourism in Croatia are based on statistical indicators, such as the level of development of tourist regions expressed through investments in infrastructure, the number of employed and the direct benefit of tourism to the economy. Despite the fact that the Continental part of Croatia abounds in tourism potential, what is offered is recognised only locally. This problem has negative impacts at the strategic level, as project planning and financing need to have a regional dimension. Some authors (Kušen, 1999; Koščak, 1998; Krippendorf, 1986; Müller, 1994; Stabler, 1996; Travis et al., 1994) have developed a cadastre of tourism potential, which has never been implemented. Therefore, this paper aims to map the tourism potentials of Continental Croatia by using the triple helix model, based on which regional tourism can be developed and future project funding ensured.